THE NEW URBANISM OF FISHERMEN’S VILLAGE IN BULAK SETTLEMENT SURABAYA - Ratna Darmiwati (Journal of Architecture&ENVIRONMENT, 2016)
Based on the existing potential characteristics, Surabaya is developed to function as the nation’s center of main area C, that covering areas in the east and north of Indonesia. The nation’s target in city development are field of industry, trading, maritime, garrison and tourism. Land condition in Surabaya is not fully urban, because there are areas with rural use such as paddy field, moor, ponds and coastal forest.  The rural use of land are found in west, south-west and eastern part of Surabaya.  The condition shows that the activity is dual, which are urban and rural.  It is related with the environment which is hilly topography at the western part of Surabaya and shore at the eastern part of Surabaya. The scope of study research is identification that is conducted in a fishermen’s settlement of Bulak, Surabaya. The identification covers physical and non physical aspects of the area. The environment and buildings’ condition,and land use are covering demography, social economic and culture condition. The research method is conducted by inventory of data, using the observation technique, interview, and documentation, moreover visual observation. The use of theory is related to the fishermen’s settlement, sense of place and new urbanism. Result of the research is a strategy concept in efforts to renewal the fisherman’s area based on physical and non physical characteristics. Consist of “Government and  community participation are  needed for renewal settlement in  fishing village. The guidance of local government was needed on various small business opportunities, where process is quite simple and profitable for low income people. They have to demonstrate the balance between ‘man-houses-environment’, so that the relation between them can be dynamic and sustainable. The existence of houses in fishing area need a private bathrooms with good sanitation and septic tanks, for environment preservation. They need to obtain good economic opportunities are promising for low income level. The some environments in coastal area need  electricity services especially in study area.